(untitled) (REMUNOM, 2025)
Introduction: Gestational Diabetes Mellitus is a condition that occurs during pregnancy, beginning in gestation, with variable intensity or detection throughout the gestational period. Thus, adequate healthcare during pregnancy is crucial for preventing or reducing maternal and infant health complications. General Objective: To analyze the importance of prenatal care in gestational diabetes. Specific Objective: To describe the care provided during prenatal follow-up related to gestational diabetes. Methodology: This study conducted a bibliographic review on the topic. The texts were collected from databases available in the Virtual Health Library (VHL), Scientific Electronic Library Online (SCIELO), and Latin American and Caribbean Health Sciences Literature (LILACS), using the terms “gestational diabetes,” “prenatal care.” Articles were selected based on inclusion criteria of relevance to the theme, published between 2014 and 2024, and written in Portuguese to facilitate comprehension. Exclusion criteria included repeated articles, incomplete texts, foreign-language publications, or those not addressing the topic.Final Considerations: It is considered that prenatal care is of utmost importance for the screening, diagnosis, and treatment of patients with gestational diabetes or predisposition to the condition, preventing potential complications.